THE USE OF METAPHORS IN LITERARY TEXTS IN ENGLISH AND UZBEK - Nargiza Suyarova; Jasmina Ismatova (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Metaphor is a fundamental stylistic device in literature that enriches language,  conveys  abstract  concepts,  and  evokes  emotional  responses.  This  study explores the use of metaphors in literary texts in English and Uzbek, highlighting both universal  and  culture-specific  features.  The  paper  examines  how  metaphorical expressions reflect cultural values, worldview, and cognitive patterns in each language. Comparative  analysis  reveals  similarities  in  metaphorical  mechanisms  while emphasizing the influence of cultural context on metaphorical choices. The findings contribute to a deeper understanding of cross-cultural literary analysis and translation studies.